Analysis of Development of Mango Fruit Juice Beverage Products Using the QFD (Quality Function Deployment) method at the "SO Food Drink" UMKM Kendari City - Sitti HAJJAH Awaliyah; Sarinah Sarinah; Sakir Sakir (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2022)
This study aims to determine the development of mango fruit juice drink products using the QFD (Quality Function Deployment) method in "So Food Drink" UMKM in Kendari City. The determination of the research location was carried out purposively. Data collection was carried out using observation, questionnaires, interviews and documentation. The analytical method used is Quality Function Deployment (QFD). The results showed that the process of developing mango juice drink products in UMKM "So Food Drink" using the QFD method found that those that were prioritized for development were by consumer expectations, successively including (1) listed expiration date (11.20%); (2) product resistance at room temperature (10.07%); (3) attractive packaging design (8.89%); (4) ease of obtaining mango juice drink products (8.44%), (5 not using hazardous materials (7.96%); (6) taste that does not change (7.85%); (7) taste sweet (7.85%); (8) has a long shelf life in the refrigerator (7.79%); (9) thick texture (7.70%); (10) has a brand label (7.58%) (11) economical packaging (7.49%), and (12) no sour taste (7.19%) Technical requirements or technical response for mango juice drink products brand "So Food Drink" to fulfil desires and consumer needs start from (1) sorting mangoes; (2) fruit mixer/crushing; (3) packaging/labelling; (4) shelf life/temperature; and (5) marketing/promotion.